Quantitative proteomics identifies tumour matrisome signatures in patients with non-small cell lung cancer - Titmarsh, Helen F.; von Kriegsheim, Alex; Wills, Jimi C.; O’Connor, Richard A.; Dhaliwal, Kevin; Frame, Margaret C.; Pattle, Samuel B.; Dorward, David A.; Byron, Adam; Akram, Ahsan R. (Frontiers in Oncology, 2023)
Abstract Introduction: The composition and remodelling of the extracellular matrix (ECM) are important factors in the development and progression of cancers, and the ECM is implicated in promoting tumour growth and restricting anti-tumour therapies through multiple mechanisms. The characterisation of differences in ECM composition between normal and diseased tissues may aid in identifying novel diagnostic markers, prognostic indicators and therapeutic targets for drug development. Methods: Using tissue from non-small cell lung cancer (NSCLC) patients undergoing curative intent surgery, we characterised quantitative tumour-specific ECM proteome signatures by mass spectrometry. Results: We identified 161 matrisome proteins differentially regulated between tumour tissue and nearby non-malignant lung tissue, and we defined a collagen hydroxylation functional protein network that is enriched in the lung tumour microenvironment. We validated two novel putative extracellular markers of NSCLC, the collagen cross-linking enzyme peroxidasin and a disintegrin and metalloproteinase with thrombospondin motifs 16 (ADAMTS16), for discrimination of malignant and non-malignant lung tissue. These proteins were up-regulated in lung tumour samples, and high PXDN and ADAMTS16 gene expression was associated with shorter survival of lung adenocarcinoma and squamous cell carcinoma patients, respectively. Discussion: These data chart extensive remodelling of the lung extracellular niche and reveal tumour matrisome signatures in human NSCLC.